2022
DOI: 10.1002/adsc.202200900
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Asymmetric 1,6‐Addition of Borylalkene‐Derived Nucleophiles to para‐Quinone Methides

Abstract: Herein, we report the catalytic 1,6‐addition of chiral alkyl copper nucleophiles, in‐situ generated from borylalkenes and a copper‐hydride catalyst under mild conditions. Chemo‐ and stereoselective control was crucial in this reductive coupling process of borylalkenes and para‐quinone methides, sequentially forming adjacent stereogenic centers with good diastereo‐ and enantioselectivity. Through the multicomponent and catalytic tandem reactions, asymmetric 1,6‐adducts of p‐quinone methides were efficiently syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Yin et al reported a 1,6-addition of borylalkene derivatives into para-quinone methides (Scheme 38b). 138 From 2019 to 2021, the reductive coupling reactions of several cyclic or acyclic dienes with aldehydes or ketones were reported to provide b-allyl quaternary chiral alcohols (Scheme 38c). 139 In 2016, Liu and Buchwald et al discovered for the first time the reductive coupling of 1,3-butadienyne and ketone.…”
Section: Allylationmentioning
confidence: 99%
“…Yin et al reported a 1,6-addition of borylalkene derivatives into para-quinone methides (Scheme 38b). 138 From 2019 to 2021, the reductive coupling reactions of several cyclic or acyclic dienes with aldehydes or ketones were reported to provide b-allyl quaternary chiral alcohols (Scheme 38c). 139 In 2016, Liu and Buchwald et al discovered for the first time the reductive coupling of 1,3-butadienyne and ketone.…”
Section: Allylationmentioning
confidence: 99%
“…A wider arsenal of nucleophilic partners is accessible to procedures that engage stable, preisolated p-QMs, but this requires that the latter are α-di-tertbutyl and/or δ-aryl substituted. [21,[24][25][26][27] Recently, our group became interested in the development of synthetic methodology for benzylic functionalization of phenolics extracted by reductive catalytic fractionation (RCF) of lignocellulosic biomass. In this context, we explored a strategy that involves the straight-forward electrochemical conversion of biomass-derived monomers into benzyl HFIP ethers, followed by base-metal catalyzed introduction of synthetically useful moieties (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, p ‐QM release is almost always achieved under acidic conditions, [17,18,20–23] which reduces the scope of amenable nucleophiles and consequently the chemical nature of functionalities that can be installed. A wider arsenal of nucleophilic partners is accessible to procedures that engage stable, pre‐isolated p ‐QMs, but this requires that the latter are α ‐di‐ tert ‐butyl and/or δ ‐aryl substituted [21,24–27] …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of the Cu-catalyzed reductive coupling of unsaturated compounds with π-electrophiles for asymmetric synthesis has received increasing attention for producing useful organic frameworks . During the past decades, our group and others have utilized alkenyl boron compounds as novel starting substrates for the asymmetric synthesis of chiral organoboron compounds since our first use of an alkenylboron derivative containing a 1,8-diaminatonaphthalene (dan) ligand in Cu-catalyzed asymmetric hydroboration . Therefore, we decided to develop a new C–C bond-forming approach to chiral β-aminoboronates through the reductive coupling of acyclic imines with vinylboron derivatives containing an encumbered boron substituent.…”
mentioning
confidence: 99%